Evaluating the relative impacts of operational and financial factors on the competitiveness of an algal biofuel production facility. (November 2016) - Hise, Adam M.; Characklis, Gregory W.; Kern, Jordan; Gerlach, Robin; Viamajala, Sridhar; Gardner, Robert D.; Vadlamani, Agasteswar
Graphical abstract: Highlights: Algal biofuel processes evaluated relative to operational and financing scenarios. Lipid productivity and conversion method affect the value of novel techniques. Investment incentives promote pathways with greater capital intensity. Operating and financing assumptions affect choice of cost-competitive pathway. Abstract: Algal biofuels are becoming more economically competitive due to technological advances and government subsidies offering tax benefits and lower cost financing. These factors are linked, however, as the value of technical advances is affected by modeling assumptions regarding the growth conditions, process design, and financing of the production facility into which novel techniques are incorporated. Two such techniques, related to algal growth and dewatering, are evaluated in representative operating and financing scenarios using an integrated techno-economic model. Results suggest that these techniques can be valuable under specified conditions, but also that investment subsidies influence cost competitive facility design by incentivizing development of more capital intensive facilities (e.g., favoring hydrothermal liquefaction over transesterification-based facilities). Evaluating novel techniques under a variety of operational and financial scenarios highlights the set of site-specific conditions in which technical advances are most valuable, while also demonstrating the influence of subsidies linked to capital intensity.